PROTOTYPE SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KAMERA DIGITAL - Yumarlin Yumarlin MZ (Informasi Interaktif, 2018)
Often times consumers have difficulty in determining the brand and type of digital camera that will be purchased, this is due to so many brands and competitive prices offered by the digital camera manufacturer. Required a system that can select and classify criteria selected by consumer.The purpose of this research is to design and build prototype of digital camera selection decision system that can help provide solution and recommendation to prospective buyer of digital camera using MADM (Multi Atribute Dicision Making) with Weighted Product (WP) method. The prototype of this decision support system is designed to have six digital camera criteria including camera brands desired by potential buyers, prices from digital cameras, resolutions desired by buyers, desired zoom size, camera lenses and batteries from digital cameras. according to the needs and criteria desired.  Keyword: Multi Atribute Dicision Making, Kamera Digital, Weighted Product